240-GHz Reflectometer with Integrated Transducer for Dielectric Spectroscopy in a 130-nm SiGe BiCMOS Technology - Defu Wang; Mohamed Hussein Eissa; Klaus Schmalz; Thomas Kämpfe; Dietmar Kissinger (2020 IEEE/MTT-S International Microwave Symposium (IMS), 2020)
This paper presents a reflectometer with an integrated transducer as a high-integration miniaturized sensor for dielectric spectroscopy at 240 GHz in SiGe BiCMOS technology. The reflectometer consists of a signal generation component using 240-GHz multiplier chains, side-coupled directive couplers and a two-channel heterodyne receiver. Readout of the transducer upon exposure to liquids is performed by the measurement of its reflected signal using an external excitation source. The experimental dielectric sensing is demonstrated by using a binary methanol-ethanol mixture placed on the proposed on-chip dielectric sensor in the assembled printed circuit board.